(untitled) (Research, Society and Development, 2022)
The family budget was affected by the COVID-19 pandemic, mainly due to the stoppage of several commercial establishments, and eating habits have changed due to reduced access to food, and a worsening in their nutritional quality. The objective of this study was to evaluate the family budget and food consumption of residents of Rio Paranaíba - MG before and during the COVID-19 pandemic. The exploratory, descriptive and quantitative study took place through a semi-structured online questionnaire prepared in Google Forms. Data are presented in absolute and relative frequencies. Most of the evaluated were female and were up to 40 years old. There was an impact on the family budget, as before the pandemic 31.53% of respondents had an income between 1 and 2 minimum wages, and during the pandemic 50.74% had such income, a fact that changed some eating habits, as some reported that during the pandemic they did not eat fruit, vegetables, meat and milk on any day of the week; and among those who ate such foods daily, there was a reduction in their consumption. Most reported not eating processed foods during the pandemic, suggesting that the longer time at home due to social isolation, made it possible to prepare and consume healthier foods such as fruits and vegetables. It was concluded that there is a need for discussions about public policies that can contribute to improvements in the budget of these families in Rio Paranaíba to increase the purchasing power of food that impact their quality of life.